2018
DOI: 10.3390/coatings8060207
|View full text |Cite
|
Sign up to set email alerts
|

Application of Nanofibrillated Cellulose on BOPP/LDPE Film as Oxygen Barrier and Antimicrobial Coating Based on Cold Plasma Treatment

Abstract: The application of nanofibrillated cellulose (NC) films in packaging industry has been hindered by its lack of heat-sealing ability. Incorporation of NC films with the biaxially oriented polypropylene/low density polyethylene (BOPP/LDPE) laminates can take advantage of each material and endow the films with novel functions for food packaging applications. In this study, a coating that consists of NC and nisin was applied onto a cold plasma treated BOPP/LDPE film to fabricate a novel active packaging with an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 52 publications
2
20
0
Order By: Relevance
“…CP exerts varying effects on structural, mechanical, thermal, and barrier properties of packaging materials, with power, holding time, carrier gas, and polymer nature standing as the most influential parameters on surface modification: no adverse effect on glass transition temperature, overall migration and oxygen/WVP, and improved thermal stability of PLA (Pankaj et al, 2014); structural changes and reduced barrier properties of PP due to etching and degradation (Vishnuvarthanan & Rajeswari, 2015); increased tensile strength, elongation, lightness, printability (ink adhesion), moisture barrier properties, glass transition temperature and biodegradability of defatted soybean meal (DSM)-based edible film, and limited oxygen availability due to CP polymer crosslinking (Oh, Roh, & Min, 2016); no adverse effect on surface temperature, optical characteristics, tensile strength, and straininduced deformation of glass, PE, PP, and nylon and paper foil (Puligundla et al, 2016); lower WVP and higher tensile strength of bilayer Zataria multiflora EO-coated PP/CMC films (Honarvar et al, 2017); increased tensile strength of alginate-chitosan/LDPE, with lower solubility for chitosan-based films (Rahmani et al, 2017); significant changes in elongation at break and crosslinking, but unchanged thermal stability and flexural properties of starch/PET films (Wiącek et al, 2017); improved oxygen barrier properties, tensile strength, and elongation at break of whey-protein-coated PET (Joo et al, 2018); satisfying mechanical properties and transparency of BOPP/LDPE films coated with nanofibrillated cellulose and nisin (Lu et al, 2018); antifogging and highly transparent properties of PVA thin films (Paneru et al, 2019); and decreased WVP and solubility of fish protein films Romani et al, 2019. Besides surface sanitization and enabling of microbicidal coatings/gels (Section 6.1), enhanced microbiological food safety and quality have also been recorded for CP-treated polymers: retarded lipid oxidation and reduced hardness of smoked salmon packaged in CP-treated DSM films during storage at 4 • C (Oh et al, 2016); unaffected color, lipid peroxidation, sarcoplasmic protein denaturation, nitrate/nitrite uptake, or myoglobin isoform distribution of CP-treated vacuum-packaged beef loins after 10 days followed by a 3-day aerobic storage at 3 • C (Bauer et al, 2017); and improved release of thyme EO (TO) after CP treatment of TO/silk fibroin nanofibers, leading to approximately 6.1 log/g reductions of S. Typhimurium in chicken and duck meat (Lin, Liao, et al, 2019). Furthermore, in-package CP technology, namely, the ability to generate CP inside a sealed package, and its combination with modified atmosphere packaging (MAP) have gained growing interest in recent years as a food surface decontamination technology (please refer to Ekezie e...…”
Section: Impact Of Innovative Food Processing On Package Performance mentioning
confidence: 99%
“…CP exerts varying effects on structural, mechanical, thermal, and barrier properties of packaging materials, with power, holding time, carrier gas, and polymer nature standing as the most influential parameters on surface modification: no adverse effect on glass transition temperature, overall migration and oxygen/WVP, and improved thermal stability of PLA (Pankaj et al, 2014); structural changes and reduced barrier properties of PP due to etching and degradation (Vishnuvarthanan & Rajeswari, 2015); increased tensile strength, elongation, lightness, printability (ink adhesion), moisture barrier properties, glass transition temperature and biodegradability of defatted soybean meal (DSM)-based edible film, and limited oxygen availability due to CP polymer crosslinking (Oh, Roh, & Min, 2016); no adverse effect on surface temperature, optical characteristics, tensile strength, and straininduced deformation of glass, PE, PP, and nylon and paper foil (Puligundla et al, 2016); lower WVP and higher tensile strength of bilayer Zataria multiflora EO-coated PP/CMC films (Honarvar et al, 2017); increased tensile strength of alginate-chitosan/LDPE, with lower solubility for chitosan-based films (Rahmani et al, 2017); significant changes in elongation at break and crosslinking, but unchanged thermal stability and flexural properties of starch/PET films (Wiącek et al, 2017); improved oxygen barrier properties, tensile strength, and elongation at break of whey-protein-coated PET (Joo et al, 2018); satisfying mechanical properties and transparency of BOPP/LDPE films coated with nanofibrillated cellulose and nisin (Lu et al, 2018); antifogging and highly transparent properties of PVA thin films (Paneru et al, 2019); and decreased WVP and solubility of fish protein films Romani et al, 2019. Besides surface sanitization and enabling of microbicidal coatings/gels (Section 6.1), enhanced microbiological food safety and quality have also been recorded for CP-treated polymers: retarded lipid oxidation and reduced hardness of smoked salmon packaged in CP-treated DSM films during storage at 4 • C (Oh et al, 2016); unaffected color, lipid peroxidation, sarcoplasmic protein denaturation, nitrate/nitrite uptake, or myoglobin isoform distribution of CP-treated vacuum-packaged beef loins after 10 days followed by a 3-day aerobic storage at 3 • C (Bauer et al, 2017); and improved release of thyme EO (TO) after CP treatment of TO/silk fibroin nanofibers, leading to approximately 6.1 log/g reductions of S. Typhimurium in chicken and duck meat (Lin, Liao, et al, 2019). Furthermore, in-package CP technology, namely, the ability to generate CP inside a sealed package, and its combination with modified atmosphere packaging (MAP) have gained growing interest in recent years as a food surface decontamination technology (please refer to Ekezie e...…”
Section: Impact Of Innovative Food Processing On Package Performance mentioning
confidence: 99%
“…This composite film will present the advantages from both materials. Peng Lu et al [ 104 ] have demonstrated that these cellulose nanofibers can also be loaded with various antimicrobial agents, like nisin for example, to enhance the film properties ( Figure 3 ). PE and PP films have been treated with cold plasma in order to improve hydrophilic character and to make them compatible with cellulose fibers.…”
Section: Antimicrobial Packaging Obtained By Modification Of Currementioning
confidence: 99%
“… Coating of polypropylene/polyethylene (PP/PE) films with other polymers (cellulose fibers—CF) and loading with antibacterial agents (nisin)—adapted after information presented in [ 104 ]. …”
Section: Figurementioning
confidence: 99%
“…In a more recent work, coatings based on MFC and nisin have been incorporated with the biaxially oriented polypropylene/low density polyethylene (BOPP/LDPE) laminates to create an antimicrobial packaging. As a result, the coated laminates showed better oxygen barrier compared to the uncoated ones (24.02 vs. 67.03) and exhibited antimicrobial properties, with a growth inhibition of L. monocytogenes by 94% [82]. From this global research effort, a new door is opened, that of using a safe and more sustainable material like the NC in replacement with the resins gas barrier currently used in food packaging.…”
Section: Why Focus On Nanocellulose Coatings?mentioning
confidence: 99%